المنهاج التربوي ودوره في بناء وتفعيل منظومة القيم داخل المجتمع - أبيش, سمير (جامعة الوادي - University of Eloued, 2021)
لأن كانت هنالك مؤسسات اجتماعية كثيرة تساهم في عملية بناء وتوليد الشعور القيمي داخل المجتمع، فإننا على يقين أن مؤسس المدرسة تمثل أنجع هذه المؤسسات وأقدرها على القيام بهذا الدور، ليس دور البناء فقط وإنما دور تفعيل هذه القيم وجعلها ماثلة في سلوك الأفراد وذلك هو الأهم كما أشار بن نبي رحمه الله، ويرجع هذا الدور الفعّال للمدرسة لما تتميز به من خصائص تميزها عن غيرها من إلزامية منهجها وطول مدة المكوث داخلها والتي قد تصل إلى 23 سنة، وهي مدة كافية لإحداث أي تغيير في سلوك الإنسان، وتقوم المدرسة بدورها في بناء وتفعيل منظومة القيم بالأساس من خلال منهجها التربوي الذي تعمل عبر تضمينه جملة القيم المرغوبة وغير المرغوبة وإكسابها للتلاميذ في شكل مقررات دراسية ونشاطات صفية ولاصفية بواسطة (المعلم والكتاب المدرسي)، فالمعلم بما ينقله للتلاميذ من القيم والكتاب المدرسي بما يتضمنه من قيم يعمل المعلم على ترجمتها للتلاميذ. الكلمات المفتاحية: المدرسة؛ المنهاج التربوي؛ القيم؛ المجتمع المسلم؛ المعلم. Abstract: Because there were many social institutions that contribute to the process of building and generating a sense of values within the community, we are sure that the founder of the school represents the most effective and capable of these institutions to play this role, not only the role of construction, but the role of activating these values and making them present in the behavior of individuals and this is the most important Bin Nabi, may God have mercy on him, pointed out, and this effective role of the school is due to its characteristics that distinguish it from other compulsory curricula and the length of stay inside it, which may reach 23 years, which is sufficient to effect any change in human behavior The school plays its role in building and activating the system of values mainly through its educational curriculum, which works by including the set of desired and undesirable values and providing them to students in the form of academic courses and class and extra-curricular activities through (the teacher and the textbook). The teacher translates it for the pupils.
The educational curriculum and its role in building and activating the value system within society
مقال
Keywords: المدرسة ، منهاج التربية ، المعلم، المجتمع المسلم ، القيم; School, Educational curriculum, Value, Muslim community, the teacher.